MD simulation of organics adsorption from aqueous solution in carbon slit-like pores. Foundations of the pore blocking effect - Gauden, P.; Terzyk, A.; Furmaniak, S.; Wloch, J.; Kowalczyk, Poitr; Zielinski, W. (Institute of Physics Publishing Ltd., 2014)
The results of systematic studies of organics adsorption from aqueous solutions (at the neutralpH level) in a system of slit-like carbon pores having different sizes and oxygen groups located at the pore mouth are reported. Using molecular dynamics simulations (GROMACSpackage) the properties of adsorbent–adsorbate (benzene, phenol or paracetamol) as well as adsorbent–water systems are discussed. After the introduction of surface oxygen functionalities, adsorption of organic compounds decreases (in accordance with experimental data) and this is caused by the accumulation of water molecules at pore entrances. The pore blocking effect decreases with the diameter of slits and practically vanishes for widths larger than approx. 0.68 nm. We observed the increase in phenol adsorption with the rise in temperature. Moreover, adsorbed molecules occupy the external surface of the slit pores (the entrances) in the case of oxidized adsorbents. Among the studied molecules benzene, phenol and paracetamol prefer an almost flat orientation and with the rise in the pore width the number of molecules oriented in parallel decreases. The decrease or increase in temperature (with respect to 298 K) leads to insignificant changes of angular orientation of adsorbed molecules.